Synthesis, structural, strength and corrosion properties of thin films of the type CuX (X = Bi, Mg, Ni) - Kozlovskiy, A. L.; Zdorovets, M. V. (Journal of materials science. Materials in electronics, 2019)
Absract The paper presents the results of studying of structural and phase properties of films based on copper–bismuth, copper–magnesium, copper–nickel, obtained by the method of electrochemical deposition. The dependences of the influence of the synthesis conditions on the phase composition and the strength and corrosion properties of the synthesized films are established. Interest in two-component films based on selected metals is due to their structural properties and the prospect of using them as protective coatings. The choice of elements of bismuth, magnesium and nickel in combination with copper is due to the possibility of obtaining structures with different phases, which can have a significant impact on the corrosion properties of films when interacting with aggressive media. During tests for corrosion resistance, it was found that a decrease in the concentration of copper and copper-containing phases leads to an increase in resistance to degradation and oxidation of thin films.